Be my valenslime! - Tarantino, Kris; Doerrfeld, Cori (Colorado Springs, Colorado WaterBrook, 2023)
Snoodle sets out to throw he perfect Valentine's Day party for her monster friends, but when nothing goes according to plan, she models the biblical definition of love from 1 Corinthians 13 and proves that love is worth celebrating.
112787
Keywords: Love -- Juvenile fiction; Monsters -- Juvenile fiction; Valentine's Day -- Juvenile fiction; Christian life -- Juvenile fiction; Christian fiction; Picture books